Pengembangan Potensi Masyarakat Desa Cianaga Melalui Program Pariwisata Dan Ekonomi Kreatif - Septiadi, Firman; Leonita Siwiyanti; Nuriman (Jurnal Visi Pengabdian Kepada Masyarakat, 2024)
The purpose of this community service after the COVID-19 pandemic is to improve the tourism sector and creative economy in Cianaga Village, Sukabumi Regency. MSME and tourism mapping shows untapped potential. The village faces problems such as being in a disaster-prone area and not many people know about the creative economy opportunities. Students of KKN Universitas Muhammadiyah Sukabumi work together with local governments and village patriots to increase public understanding of tourism, creative economy, and the use of digital technology through counseling and mentoring. Tourismassistance, MSME product development, entrepreneurship training, and digital marketing are some forms of community service. Mapping of small and medium enterprises (MSMEs) found that several business actors actively produce superior products. Becausethis village arena is under the foothills of Mount Halimun Salak which is prone to landslides, disaster mitigation counseling is also carried out. MSME players receive intensive assistance to improve product quality and marketing. One result is an integrated travel web, increased public understanding of the creative economy, and active participation in disaster reduction. Overall, this community service can improve the economy and welfare of Cianaga Village.